AN OVERVIEW ON INFECTION PREVENTION AND CONTROL PRACTICES AND BIOMEDICAL WASTE MANAGEMENT (BMWM) IN COVID-19 ERA - SHARMA, RAVI PRAKASH; DUTTA, SIDDHARTHA; MISHRA, GOVIND; LAL, HINA; KUMAR, TARUN; SHARMA, ANU (International Journal of Current Pharmaceutical Research, 2020)
The ongoing Coronavirus disease (COVID-19) pandemic has affected the almost entire world and has hit the healthcare and economic sector with a hard blow. The Government imposed lockdowns in almost all part of the world has not only affected the global economy but also has harsh effects on physical and mental health of people around the world. To date, there is no specific and defined treatment or vaccine available for its prophylaxis and treatment; hence preventive strategies like Infection prevention and control (IPC) practices and proper disposal of biomedical waste (BMW) play key role in preventing transmission of the infection in the healthcare sector among healthcare professionals. Ethically, we all should follow the IPC and BMW guidelines soulfully to prevent ourselves and fellow workers from getting infected. The review highlights the salient features of the IPC and BMWM (Biomedical waste management) practices in concise manner for better understanding and implementation at this crucial period of COVID-19 pandemic.